Detection Of Group B Rotavirus In Buffalo Calves In Haryana State Of Northern India - Mohan, Hari; Minakshi; Kumar, Pawan; Prasad , G (Indian Journal of Veterinary Sciences and Biotechnology, 2011)
Group B rotaviruses have been found associated with sporadic cases of diarrhea in calves and adult cows. One hundred fifty six faecal samples were collected from diarrheic buffalo calves under six months of age and tested for group B rotaviruses by polyacrylamide gel electrophoresis (PAGE) and reverse transcription (RT)-PCR by targeting 260 & 961 bp of VP3 and VP4 genes, respectively). By RNA-PAGE, seven calf samples were group B rotavirus positive (long electropherotype) and all the samples were found positive by RT-PCR. To the best of our knowledge, this is the first report on the presence of buffalo group B rotavirus in Haryana state of Northern India.
Keywords: Electropherotypes; Group A rotavirus; Group B rotavirus; RNA-PAGE; RT-PCR